2020
DOI: 10.48550/arxiv.2008.01039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spiking neuromorphic chip learns entangled quantum states

Stefanie Czischek,
Andreas Baumbach,
Sebastian Billaudelle
et al.

Abstract: Neuromorphic systems are designed to emulate certain structural and dynamical properties of biological neuronal networks, with the aim of inheriting the brain's functional performance and energy efficiency in artificial-intelligence applications [1,2]. Among the platforms existing today, the spike-based BrainScaleS system stands out by realizing fast analog dynamics which can boost computationally expensive tasks [3]. Here we use the latest BrainScaleS generation [4] for the algorithm-free simulation of quantu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Other recent work has shown that quantum spin-based Ising systems, including probability distributions corresponding to those seen in quantum entanglement, can be learned and emulated by networks of leaky integrateand-fire spiking neurons on VLSI chips. These implementations effectively architect positive operator-valued measures (Czischek et al, 2021). Our work is complementary and consistent with such work since we effectively architect linear, nonspiking classical analog quadrature oscillator circuits to represent phase.…”
Section: Introductionsupporting
confidence: 57%
“…Other recent work has shown that quantum spin-based Ising systems, including probability distributions corresponding to those seen in quantum entanglement, can be learned and emulated by networks of leaky integrateand-fire spiking neurons on VLSI chips. These implementations effectively architect positive operator-valued measures (Czischek et al, 2021). Our work is complementary and consistent with such work since we effectively architect linear, nonspiking classical analog quadrature oscillator circuits to represent phase.…”
Section: Introductionsupporting
confidence: 57%
“…Due to the physical implementation the emulation becomes inherently parallel, rendering the sampling speed independent of the network size. We note that neuromorphic hardware has recently been used to represent entangled quantum states using a mapping of general mixed quantum states to a probabilisitic representation and training the system to represent a given state by approximating its corresponding probability distribution [19]. Here, instead, we directly encode the wave function of pure quantum states and use this approach for variational ground state search through minimization of the quantum system's total energy (Fig.…”
Section: Introductionmentioning
confidence: 99%